Using HIV/AIDS interventionist research in a university context to improve women's sexual and reproductive health awareness - Kidia, Nitasha (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Background: Young women in South Africa are a vulnerable group, with HIV prevalence almost twice that of men, limited preventive behaviour, and many challenges in negotiating sex. However, there is a paucity of in-depth research to understand how these challenges play out and what can be done to promote positive sexual and reproductive health in this population. Methods: To understand the effects of the Auntie Stella Activity card intervention (developed and used in Zimbabwe), this study used a mixed methods participatory action research design. Five focus group discussions among female Rhodes University students between the ages of 18- 23 were conducted with the activity cards as a basis for engagement. Additionally, pre-and postintervention sexual and reproductive health awareness levels were also measured by a customized questionnaire. Based on participants' responses to the cards and post-exposure reflections on their learning, possible impacts on behaviour change were explored. Thematic analysis of transcripts was used to draw out major themes in the qualitative data. Results and conclusions: Themes that emerged were: 1) women's self-esteem; 2) lack of knowledge; 3) peer pressure and male dominance; and 4) alcohol and substance use. Results of the pre- and post- intervention questionnaire found a positive change in knowledge and behaviour amongst the participants. However, the intervention in its current format focused too much on teenage rather than adult scenarios. To make it more useful for this population, further modifications that account for the target age group are needed. Overall, the challenges in sexual and reproductive health faced by university-aged women in South Africa are deeply concerning, but this study's findings show that an intervention like the ASAC has the potential to be used widely in Southern Africa, if appropriately tailored.
Keywords: HIV infections -- Prevention -- South Africa; AIDS (Disease) -- Prevention -- South Africa; AIDS (Disease) -- Study and teaching -- South Africa; Health education (Higher) -- South Africa; Sex instruction -- South Africa; College students -- Sexual behavior -- South Africa; Sex instruction for women -- South Africa; Women college students -- Psychology -- South Africa; Women -- Health and hygiene -- South Africa; Women -- Diseases -- Prevention -- South Africa